Pola Penyebaran Fruktosa, Glukosa, dan Sukrosa pada Bagian-Bagian Umbi Bulbus Berbagai Kultivar Bawang Bombay - Suharwadji Sentana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
This study was desiged to find out the distribution patterns of fructose, glucose and sucrose of Southport White Globe, early Lockyer White and White Spanish onions. Ten onions bulbs were each divided into three parts : top, middle, and bottom. Each part was then divided into three layers of scales : outside, middle, and centre scales. The idividual sugar contents of each part were then determined. The results showed that fructose content at the tops of the three onion cultivars tended to be lower towards bottom of the bulbs at different rate, depending on the layer of scales and cultivars. On the other hand, fructose contents of the outside towards the centre and glucose and sucrose content of the bulb parts of the three cultivars showed no special distribution patterns.